Requiem - Oliver, Lauren 1982- (New York, NY Harper, 2013)
"While Lena navigates the increasingly dangerous Wilds, her best friend, Hana, lives a safe, loveless life in Portland."--
Sequel to: Pandemonium
1
Keywords: Best friends -- Fiction; Friendship -- Fiction; Government, Resistance to -- Fiction; Love -- Fiction; Marriage -- Fiction; Science fiction; Maine -- Fiction